Linearization of double-infinite Toda lattice by means of inverse spectral problem - Berezansky, Yu. M. (Methods of Functional Analysis and Topology, 2012)
The author earlier in [3, 4, 6, 7] proposed some way of integration the Cauchy problem for semi-infinite Toda lattices using the inverse spectral problem for Jacobi matrices. Such a way for double-infinite Toda lattices is more complicated and was proposed in [9]. This article is devoted to a detailed account of the result [3, 4, 6, 7, 9] . It is necessary to note that in the case of double-infinite lattices we cannot give a general solution of the corresponding linear system of differential equations for spectral matrix. Therefore, in this case the corresponding results can only be understood as a procedure of finding the solution of the Toda lattice.